PENGARUH METODE PEMBELAJARAN DAN SARANA PRASARANA TERHADAP PENGETAHUAN HYGIENE MAKANAN MAHASISWA PRODI TATA BOGA - Sri Bayu; Welrohip Samosir; Laurena Ginting; Vina Gabriella Saragih (STKIP Subang, 2025)
This study aims to analyze the influence of learning methods, infrastructure, and practicum intensity on the knowledge of food hygiene of Culinary Studies Program students. The research uses a quantitative approach with a survey method. The research instrument was in the form of a questionnaire which was distributed through Google Form to 40 Culinary students. The data were analyzed through validity, reliability, and multiple linear regression tests. The results showed that the three independent variables, namely learning methods, infrastructure, and practicum intensity, had a simultaneous significant effect on students' food hygiene knowledge (p < 0.05). Partially, varied and interactive learning methods have been proven to increase student understanding, adequate infrastructure to support the application of hygiene principles, and high practicum intensity to strengthen students' skills and awareness of food hygiene. These findings confirm the importance of the combination of these three factors in improving the quality of culinary learning. This research provides practical implications for study program managers to develop teaching methods, improve practice facilities, and increase the frequency of practicum as an effort to strengthen students' food hygiene knowledge.